2021
DOI: 10.1186/s12863-021-00998-9
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome sequence of a non-toxigenic Corynebacterium diphtheriae strain from a hospital in southeastern China

Abstract: Background Sporadic cases of infection with non-toxigenic Corynebacterium diphtheriae (C. diphtheriae) isolates have been reported in regions covered by the Diphtheria-Tetanus-Pertussis vaccine, but no information describing the whole genome of non-toxigenic strains collected in China is available. Therefore, in this work, the complete genome of a non-toxigenic strain of C. diphtheriae from a hospital located in southeastern China was performed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In recent years, several older patients carrying non-pathogenic, non-toxigenic corynebacterium diphtheria have been reported in or near Guangdong, Guangzhou [4][5][6]. The monitoring data in China indicated that most of the tetanus patients were over 40 years old, with a relatively high case fatality rate [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several older patients carrying non-pathogenic, non-toxigenic corynebacterium diphtheria have been reported in or near Guangdong, Guangzhou [4][5][6]. The monitoring data in China indicated that most of the tetanus patients were over 40 years old, with a relatively high case fatality rate [3].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent diphtheria case nationwide was reported in 2006, down from the maximum of 70.7 thousand cases (11.1 per 100,000 people) recorded from 1950-1965 [3]. However, over the last few years, patients carried non-pathogenic, non-toxigenic corynebacterium diphtheria has been increasingly reported in China, 2018 in Dongyang [4], 2022 in Zhuhai [5], 2019 [6], 2023 and 2024 in Guangzhou. The research found that the ß-corynebacteriophage can infect non-toxigenic strains, which leads to transformation to a toxigenic strain and production of the diphtheria toxin [7].…”
Section: Introductionmentioning
confidence: 99%